Lipid Droplet-Associated Proteins (LDAPs) Are Required for the Dynamic Regulation of Neutral Lipid Compartmentation in Plant Cells. Issue 4 (19th February 2016) - Gidda, Satinder K.; Park, Sunjung; Pyc, Michal; Yurchenko, Olga; Cai, Yingqi; Wu, Peng; Andrews, David W.; Chapman, Kent D.; Dyer, John M.; Mullen, Robert T.
Abstract : Lipid droplet-associated proteins play different roles in various physiological contexts and during plant stress responses. Abstract: Eukaryotic cells compartmentalize neutral lipids into organelles called lipid droplets (LD s), and while much is known about the role of LD s in storing triacylglycerols in seeds, their biogenesis and function in nonseed tissues are poorly understood. Recently, we identified a class of plant-specific, lipid droplet-associated proteins (LDAPs) that are abundant components of LD s in nonseed cell types. Here, we characterized the three LDAPs in Arabidopsis ( Arabidopsis thaliana ) to gain insight to their targeting, assembly, and influence on LD function and dynamics. While all three LDAPs targeted specifically to the LD surface, truncation analysis of LDAP3 revealed that essentially the entire protein was required for LD localization. The association of LDAP3 with LD s was detergent sensitive, but the protein bound with similar affinity to synthetic liposomes of various phospholipid compositions, suggesting that other factors contributed to targeting specificity. Investigation of LD dynamics in leaves revealed that LD abundance was modulated during the diurnal cycle, and characterization of LDAP misexpression mutants indicated that all three LDAPs were important for this process. LD abundance was increased significantly during abiotic stress, and characterization of mutant lines revealed that LDAP1 and LDAP3 were required for the proper induction of LD s during heat and cold temperature stress, respectively. Furthermore, LDAP1 was required for proper neutral lipid compartmentalization and triacylglycerol degradation during postgerminative growth. Taken together, these studies reveal that LDAPs are required for the maintenance and regulation of LD s in plant cells and perform nonredundant functions in various physiological contexts, including stress response and postgerminative growth.